Lymfadenektomie u casného karcinomu zaludku - Gatĕk, J; Duben, J; Bakala, J; Mica, T; Dudesek, B; Hasa, E; Musil, T; Hnátek, L (Rozhledy v chirurgii, 2004)
AIM: The method of extended lymphadenectomy in the early gastric carcinoma treatment remains controversial. The aim of this prospective study is to assess the above method feasibility with acceptable rates of complications, in our conditions. METHODOLOGY: From 2000 to 2003, 11 patients with early carcinomas of the stomach were treated using the method of extended lymphadenectomy. The study group included 7 males and 4 females. RESULTS: In 6 cases, the tumors were located in the distal, in 4 cases in the middle and once in the proximal third of the stomach. In a single case, the IIIA stadium was concerned, the other cases were rated lower. In total, 205 lymphonodes measuring 18.6 on average (median of 16) were examined. The total of 5 lymphonodes were malignant, all of them were found in one patient. The method of the sentinel lymphonode biopsy was applied once. A cardiopulmonary complication was reported once, a punction of the subphrenic absces was reported once, a primary disorder causing a death was reported once and the patient concerned exited after a 14-month-period of his follow-up. Once, a local relaps of the disorder was reported 43 months after the procedure. The follow-up median was 27 months. CONCLUSION: The method of extended lymphadenectomy can be conducted even in our conditions with acceptable rates of complications.
Keywords: Carcinoma; senioři; lymfadenektomie; Stomach Neoplasms; Middle Aged; mužské pohlaví; ženské pohlaví; Lymph Node Excision; Humans; nádory žaludku; Aged; Female; lidé; Male; karcinom; lidé středního věku